Mechanisms of S. agalactiae promoting G. vaginalis biofilm formation leading to recurrence of BV - Meng Li; Zhen Zeng; Xiaoqian Wang; Ying Liu; Hongbo Wei; Jun Liu; Simin Zhu; Qingyun Jiang; Ke Zhang; Yifan Wu; Shuai Liu; Juhyun Kim; et al. (npj Biofilms and Microbiomes)
Abstract Previous research has established that the formation of Gardnerella vaginalis (GV) biofilm is one of the primary reasons for bacterial vaginosis (BV) recurrence. This study was the first to explore the impact of Streptococcus agalactiae (group B Streptococcus, GBS) on GV biofilm in a co-culture scenario. The results revealed that GBS could significantly increased the GV biomass in 48-hours dual-species biofilms. The luxS gene of GBS was significantly higher in dual-species biofilm, while knockdown of the luxS gene resulted in a significant decrease in mono- and dual-species biofilms. Meanwhile, in vitro addition of AI-2 (product of luxS gene) substantially increased biofilm biomass. Furthermore, we found that the expression of two genes related to biofilm formation was notably elevated in GV after receiving AI-2 signals. Collectively, these findings suggest that GBS enhances GV biofilm formation via luxS/AI-2 in an in vitro co-culture model, which in turn may promotes recurrence of BV.